Brand Ambassador and Customer Patronage of FMCGs: Mediating Effect of Advertisement Believability (Journal of Business, Universidad del Pacífico (Lima, Peru), 2021)
The market for fast-moving consumer goods (FMCGs) in the Nigerian food and beverage industry has been inundated with a massive amount of promotional messages. These messages have resulted from intense competition and rivalry among the organizations that market similar products. The objective of this study is to evaluate the effect of a brand ambassador on the patronage of FMCGs. Furthermore, we explore the mediating role of advertisement believability in the relationship between the variables. We use a questionnaire to elicit information from 400 respondents who are members of households in the metropolitan area of Kano that consumed Peak milk. Partial least square algorithms and bootstrapping techniques served as the tools of analysis with the aid of SMART-PLS 3. Our findings indicate that a brand ambassador has an insignificant direct effect on customer patronage and that advertisement believability has no mediating effect on the influence of a brand ambassador on customer patronage. The study recommends that managers of FMCGs should use a hybrid model of a brand ambassador and believable advertising to elicit the desired patronage from their target customers. Further, they should de-emphasis the supposed role of advertisement believability as a mediating factor on the influence of a brand ambassador on customer patronage.
Keywords: Brand Ambassador, Customer, Customer Patronage, FMCGs, Mediating Effect